PF-8 Evaluation Performance Broiler in Brooding Period at Closed House and Open House - Henny Endah Anggraeni; Wilda Febrianti (Hemera Zoa, 2018)
Broiler maintenance period can be divided into two periods of starter and finisher (Muwarni 2010). Phase starter occurs in the first two weeks which is a critical period of broiler, the brooding period, the most decisive period, to the growth of the next period (Zumrotun 2012).  House is an important part of broiler maintenance. There are two types of enclosure is closed house and open house. Closed house suitable for use in areas with temperatures above 35 ◦C (Trisanto 2015).The purpose of this writing is compare the performance of broiler in brooding between closed house and open house.